Aeromagnetic Investigations Of The Northern Piedmont - Introduction - David L. Daniels (Society for Mining, Metallurgy & Exploration, 1973)
The U.S. Geological Survey has for many years been flying and compiling aeromagnetic surveys. The aim is complete coverage of the United States, about half of which is presently done. Colored aeromagnetic maps at a scale of 1:1,000,000 are published as the states are completed; Minnesota and Colorado have been published. Michigan, Iowa, Nevada, Utah, Maryland and Virginia are presently being processed. Some of the most spectacular data collected to date is from the Piedmont of the Eastern United States. I am going to discuss a preliminary aeromagnetic map of the Piedmont region between New York and North Carolina, where coverage is nearly complete. This map has been compiled from many surveys. Flight spacing over Piedmont rocks is 1/4 to 1 mile with flight elevation of 500 feet above ground. The spacing over the Virginia Coastal Plain and Valley and Ridge regions is wider at 2 - 3 miles. Much of the data in Virginia has been produced by the Virginia Division of Mineral Resources. The map is colored on a spectral color scheme with red for the higher intensities and violet the low intensities. Each color represents a 100 gamma interval. Some of the highest intensities are beyond the range of the 13 colors - these are left white. It is necessary, of course, to remove first, the Earth's main magnetic field. The Geological Survey uses the International Geomagnetic Reference Field or IGRF (Fabiano and Peddie, 1969). The use of color in aeromagnetic maps is not new, but then not common. We have found that colored aeromagnetic contour maps are more useful by far than the uncolored versions because they allow the user to instantly compare intensities in widely separated areas and visualize long wavelength anomalies even when numerous short wavelength anomalies' are superimposed. One tends to see only steep gradients on uncolored aeromagnetic maps, the broad anomalies being quite invisible. We feel that colored maps take the place of various mathematically derived maps such as second derivative or averaged maps.